Trends in urine lead and associated mortality in US adults: NHANES 1999–2018 - Wang, Qiong; Wu, Jing; Dong, Xiaoqun; Niu, Wenquan (Frontiers in Nutrition, 2024)
Objectives: This study was aimed to describe the trends of urine lead among US adults aged ≥45 years, and to explore its association with all-cause and diseasespecific mortality. Methods: This study enrolled 9669 participants from the National Health and Nutrition Examination Survey, 1999-2018. Trends of urine lead were described by Logistic regression analysis using survey cycle as a continuous variable. The Cox proportional hazards regression analyses were used to quantify the association of urine lead with mortality. Results: There was an obvious decline in urine lead concentrations from 1.203 µg/L (95% confidence interval [CI]: 1.083-1.322) in 1999-2000 to 0.478 µg/L (95% CI: 0.433 0.523) in 2017-2018, and this decline was statistically significant (P<0.001).Referring to the first tertile of urine lead concentrations, risk magnitude for all-cause mortality was significantly and linearly increased after adjustment (P=0.026 and 0.020 for partially and fully adjusted models), and significance was attained for the comparison of the third versus first tertile after full adjustment (hazard ratio [HR]:1.17, 95% CI: 1.01 to 1.35). Treating urine lead continuously, risk for all-cause mortality was statistically significant (HR: 1.18 and 1.19, 95% CI: 1.01 to 1.39 and 1.00 to 1.40 for partially and fully adjusted models). For cardiovascular diseasespecific and cancer-specific mortality, there was no hint of statistical significance. Conclusions: Our findings indicated that urine lead exhibited a declining trend from 1999-2000 to 2017-2018 in US adults aged ≥45 years, and high urine lead was a significant and independent risk factor for all-cause mortality.